ANALISIS PENGARUH BRAND AMBASSADOR, KUALITAS PRODUK DAN HARGA TERHADAP BRAND IMAGE SERTA DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Konsumen Face Care Garnier Di Kota Semarang) - Rizki, Shinta Pamudyaning; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the effect arising from the brand ambassador, product quality and price of brand image and its influence on purchase decisions of face care Garnier. Variables used in this study are brand ambassador, product quality and price as the independent variables, then brand image as intervening variable and purchase decisions as the dependent variable. The sample in this study of 200 respondents is derived from consumer face care Garnier in Semarang city. The method used is accidental sampling by distributing questionnaires to the respondents. In this study developed a theoretical model to propose six hypotheses to be tested using analysis tools Structural Equation Modeling (SEM) which is operated through a program AMOS 22.0Based on the results of data processing for the SEM full model has met the criteria of goodness of fit as follows, the value of chi-square = 97.759; probability = 0.099; RMSEA = 0.032; CMIN / DF = 1.207; GFI = 0.939; AGFI = 0.909; TLI = 0.990; CFI = 0.993; NFI = 0.959. The result of this research prove five hypothesis are accepted and one is hypothesis rejected. The five hypothesis accepted are show brand ambassador positively affect to brand image, product quality positively affect to purchase decisions, product quality positively affect to brand image,Â price positively affect to purchase decisions and brand image positively affect purchase decisions and 1 hypothesis rejected is show price is not significant but positively affected to brand image.